2019
DOI: 10.1186/s40479-019-0101-8
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported impulsivity in women with borderline personality disorder: the role of childhood maltreatment severity and emotion regulation difficulties

Abstract: Background Childhood maltreatment, such as severe emotional, physical, and sexual abuse and neglect, has been linked to impulse control problems and dysfunctional emotional coping. In borderline personality disorder (BPD), a history of childhood maltreatment may worsen difficulties in emotion regulation, which may in turn give rise to impulsive behaviours. The aim of this self-report study was to investigate associations between childhood maltreatment severity, emotion regulation difficulties, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 71 publications
8
29
0
2
Order By: Relevance
“…These results indicate that, although severe forms of childhood maltreatment are present in multiple psychiatric disorders [32], there may be differences in prevalence even between disorders with very similar phenotypes such as BPD and ADHD. These results invite the question of whether the type of childhood trauma that has been associated with the development of BPD [5,21,33] may also increase the risk of this disorder in patients with childhood ADHD.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…These results indicate that, although severe forms of childhood maltreatment are present in multiple psychiatric disorders [32], there may be differences in prevalence even between disorders with very similar phenotypes such as BPD and ADHD. These results invite the question of whether the type of childhood trauma that has been associated with the development of BPD [5,21,33] may also increase the risk of this disorder in patients with childhood ADHD.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, even with the limited evidence available, it seems that the experience of emotional abuse in children diagnosed with ADHD may be a mediating factor that increases the risk of subsequent development of BPD in adulthood. ED has been indicated as a mediator between a history of childhood maltreatment and high impulsivity in women with BPD but not in ADHD [21]. Previously, the mediating effect of ED had been described in the relationship between childhood ADHD and adult BPD in a sample of adult women diagnosed with BPD [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Missbrauch und Vernachlässigung stellen jedoch nicht nur generelle Risikofaktoren für die BPS dar, sondern wirken sich auch ungünstig auf die Symptomschwere und das Ausmaß an Komorbidität aus (McFetridge et al 2015;Quenneville et al 2020;Martín-Blanco et al 2014). Gerade Impulsivität und Schwierigkeiten in der Emotions-regulation als Kernmerkmale der BPS scheinen besonders eng mit Erfahrungen von emotionalen Misshandlungsformen in Kindheit und Jugend assoziiert zu sein (Quenneville et al 2020;Krause-Utz et al 2019;Martín-Blanco et al 2014). Allerdings bestätigen nicht alle Studien einen Zusammenhang zwischen Kindheitstraumatisierungen und Ausmaß der BPS-Symptomatik (Bungert et al 2015).…”
Section: Hintergrundunclassified
“…Conversely, with regard to personality features, it has been shown that poor emotional regulation strategies, poor emotional cognition, behavioral impulsivity, and self-criticism the increase risk of suicidal behaviors ( 14 16 ). More specifically, it has been proposed that childhood trauma may constitute an environmental risk factor for the development of impulsivity and SA in patients with depression ( 17 ), with data suggesting that childhood trauma could be related with problems in emotion regulation, which may in turn enhance impulsivity ( 18 ). However, the evidence suggests that impulsivity traits are part of a developmental cascade that increases suicide risk in a subset of suicide (not all suicides are associated with impulsive-aggressive behaviors) ( 19 , 20 ), impulsivity being one of the most accepted endophenotypes when studying suicidal behavior ( 21 ).…”
Section: Introductionmentioning
confidence: 99%